Etiology and Treatment of Growth Delay in Noonan Syndrome - Rodríguez, Fernando; Gaete, Ximena; Cassorla, Fernando (Frontiers in Endocrinology, 2021)
Noonan syndrome is characterized by multiple phenotypic features, including growth retardation, which represents the main cause of consultation to the clinician. Longitudinal growth during childhood and adolescence depends on several factors, among them an intact somatotrophic axis, which is characterized by an adequate growth hormone (GH) secretion by the pituitary, subsequent binding to its receptor, proper function of the post-receptor signaling pathway for this hormone (JAK-STAT5b and RAS/MAPK), and ultimately by the production of its main effector, insulin like growth factor 1 (IGF-1). Several studies regarding the function of the somatotrophic axis in patients with Noonan syndrome and data from murine models, suggest that partial GH insensitivity at a post-receptor level, as well as possible derangements in the RAS/MAPK pathway, are the most likely causes for the growth failure in these patients. Treatment with recombinant human growth hormone (rhGH) has been used extensively to promote linear growth in these patients. Numerous treatment protocols have been employed so far, but the published studies are quite heterogeneous regarding patient selection, length of treatment, and dose of rhGH utilized, so the true benefit of GH therapy is somewhat difficult to establish. This review will discuss the possible etiologies for the growth delay, as well as the outcomes following rhGH treatment in patients with Noonan syndrome.